The Innovation of batteries and inverters as energy saving technology without fuel - Andi Sri Irtawaty; Lilik Damayanti; Subur Mulyanto (ISAS (Indonesian Society of Applied Science), 2021)
Electrical energy is a primary need in modern human life. However, with the increase in fuel prices, the right technology is needed to overcome it, in the form of battery and inverter innovations which are combined to produce an output of 220 volts ac which has the same capacity as PLN electricity. This PkM DPRM activity was held in Manggar Village for 3 days, namely @ u on July 30, August 3 and August 4, 2020 which was attended by fishermen, fried food traders and Manggar Village employees themselves. The equipment is designed with a capacity of 300 watts and 1000 watts, tailored to the needs of the residents. The benefit greatly eases the use of diesel generator sets for fishermen, which from Rp. 108,000 / month, has now become Rp. 0, -. Likewise for fried food traders, who originally paid Rp. 70,000 / month for electricity for lighting at night, now it is Rp. 0, -. Based on the results of the questionnaire, participants are very grateful for the presence of this technology in their village. At least the motivation for other residents to implement these tools in everyday life. Keywords: power plants without fuel, save energy, fuel, lighting, manggar kelurahan